Paulo Freire and the state-of-the-art of the international journal of lifelong education. Invited article in celebration of 40 years of IJLE. Issue 6 (2nd November 2022) - Torres, Carlos Alberto; Yan, Li
ABSTRACT: This review article in celebration of the 40 th anniversary of IJLE provides an analysis of the scholarship on and about Paulo Freire in the state-of-the-art of IJLE publications between 1982–2022. The authors scanned around 4000 articles and book reviews published from 1982–2021 in the International Journal of Lifelong Education (JLE), and identified 384 articles and book reviews using the term 'Freire'. The authors assessed them, selecting 24 of them for deeper analysis. This article is divided into three sections. The first is the introduction about the importance of Freire in the field The second section is the description and analysis of the characteristics of the articles. The third section proposes new directions for research regarding Freire's oeuvre.